Late complications and sequelae of anal surgery - Praderi, Luis (Cirugía del Uruguay, 1973)
In our setting, late complications and sequelae of anal surgery due to benign conditions are happily not very frequent (38), but they do not stop be important, as some are very difficult or even impossible to cure.